An observational study on the association of nonalcoholic fatty liver disease and metabolic syndrome with gall stone disease requiring cholecystectomy. (May 2017) - Ahmed, Farah; Baloch, Qamaruddin; Memon, Zahid Ali; Ali, Iqra
Abstract: Objective: Recognition of Non alcoholic fatty liver disease (NAFLD) and metabolic syndrome in patients with gallstones undergoing laparoscopic or open cholecystectomy, along with it we will also study the life style of patients with gall stones. Background: Patients with gallstones have associated NAFLD, with concurrent metabolic syndrome and these ailments share similar factors for example obesity, hypertriglyceridemia and diabetes mellitus. Factors like body mass index, gender, raised lipid levels, use of contraceptives and alcohol and having diabetes, physical inactiveness, multiparous women, water with excessive iron content, metabolic syndrome, and NAFLD are accountable factors for gallstones formation. Methodology: This was a case series done at Surgical Unit 1 of Civil Hospital Karachi. Selective samples of 88 patients were included. Duration was 3 months. We included both sexes with ultrasound proof of gall stone irrespective of cholecystitis. Excluded patients with history of seropositive viral hepatitis, autoimmune and wilson's disease. As these conditions can act as a confounder to our variables. Results: Nafld was present in 62.5%(n = 55) while 28.4% (n = 25) had metabolic syndrome. 26.94% had BMI less than 18, 32.12 had BMI between 18 and 25 and majority had BMI greater than 25 i.e in 40.93%. Of all 46.6% had a family history of cholelithiasis. Gallstone patients with NAFLD reported about their first degree relative being suffering from cholelithiasis at a significant p-value of 0.034 while this was not significant in cases of metabolic syndrome and the p -value was 0.190. Conclusion: We found association of metabolic syndrome with gallstones and NAFLD. Non alcoholic fatty liver was highly prevalent in our study subjects. Huge percentage of first degree relatives of gall stone patients had gallstones and this relation was more pronounced patients who had associated NAFLD. Highlights: Most patients with gallstones have associated NAFLD. Metabolic syndrome, NAFLD, gallstones share common factors. We recommend health education and lifestyle modification in gall stone patients. Majority first degree relatives of gall stone patients had gallstones. First degree relatives of patients had gallstones and this relation was more pronounced patients who had associated NAFLD.